Development of a Portable Cool Box to Increase Milk Distribution Capacity - Firman Ardiansyah Ekoanindiyo; Antoni Yohanes; Endro Prihastono (Jurnal Serambi Engineering, 2024)
The SN Multipurpose Cooperative has a business of collecting pure cow's milk from dairy farmers. Milk is processed by cooling it to a certain temperature. Pure milk from cooperatives sent to milk factories can be rejected by milk factories for various reasons so that dairy farmers experience losses. The SN Multi-Business Cooperative carries out business development, namely pure milk is further processed by the cooperative into ready-to-drink processed milk products. Business development in the field of processing pure milk products will provide a greater selling value compared to pure milk sold directly to milk factories. Distribution and delivery of processed milk to consumers is carried out using motorbikes. To carry processed milk, every motorbike rider uses a basket bag made of thick cloth which is placed on the back and contains around 30 liters of milk. Inside this bag, ice cubes are placed to maintain the temperature of the processed milk. Over a long period of time the ice cubes will melt into water and seep into the basket bag and damage the basket bag. With the development of a portable toll box, it is possible to maintain milk temperature for longer as well as anthropometric arm length and upwards. The cool box installed on the motorbike is equipped with foam in the cooling box. The distributed capacity is greater to 64 liters.